Comparative analysis of CRISPR-Cas systems of Yersinia pestis and Escherichia coli strains. (November 2020 – December 2021) - Nwabunwanne, Eze Uchenna (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.